Initial/final state selection of the spin polarization in electron tunneling across an epitaxial Fe/GaAs(001) interface - Kurebayashi, H; Steinmuller, S; Laloe, J; Trypiniotis, T; Easton, S; Ionescu, A; Yates, JR; Bland, J (2007)
Spin dependent electron transport across epitaxial FeGaAs (001) interfaces has been investigated using photoexcitation techniques. Spin filtering is observed in the forward bias regime and its sign is switched by using different photon energies. First principles calculations suggest that the spin polarization of the Fe layer is positive within the energy region into which spin polarized electrons tunnel. The authors attribute this sign switching to the initial and final states of the electrons tunneling across the interface, whose spin polarizations are determined by the selection rules in GaAs during photoexcitation and spin polarization of the Fe(001) layer, respectively. © 2007 American Institute of Physics.